Réponses

Meilleure réponse !
2013-09-05T17:28:43+02:00
Bonjour
Ce sont des identités remarquables
9x² - 1 = 0
(3x-1)(3x+1) = 0
soit 3x-1 = 0 donc 3x = 1 et x = 1/3
soit 3x+1 = 0 donc 3x = -1 et x = -1/3

4x² -16 = 0
(2x-4)(2x+4) = 0
soit 2x-4 = 0 donc 2x = 4 et x = 2
ou idem pour la 2ème et x = -2

(2x-4)(2x+4) = 0 est résolu au dessus
(2x+3)(2x+1) = 0
soit 2x+3 = 0 donc 2x = -3 et x = -3/2
ou 2x+1 =0 donc 2x = -1 et x = -1/2

(4x-5)(2x+6) = 0
soit 4x-5 = 0 donc 4x = 5 et x = 5/4
soit 2x+6 = 0 donc 2x = -6 et x = -6/2 = -3

8² -8x -15 = 0
64 -8x -15 = 0
-8x = -64+15
-8x = -49
x = 49/8